A PILOT CLINICAL STUDY OF TREATING RHEGMATOGENOUS RETINAL DETACHMENT BY SILICONE RUBBER BALLOON SCLERAL BUCKLING. Issue 10 (October 2020) - Zhang, Baike; Li, Cheng; Jia, Yong; Li, Xiaodan; Guo, Lisha; Wang, Chunlei; Tian, Xuemin
Abstract : Purpose: To evaluate the efficacy and primary safety of treating rhegmatogenous retinal detachment (RRD) using foldable capsular vitreous body scleral buckling. Methods: Five patients with simple RRD were treated with foldable capsular vitreous body scleral buckling. B-ultrasound and fundus photography examining of retina reattachment were used to evaluate the postsurgery efficacy. The safety of the treatment was evaluated based on the occurrence of infection, eye pain, diplopia, elevated intraocular pressure, and other serious postoperative complications after surgery. The observation time after the operation was at least 12 weeks. Results: The simple RRD of all five patients was successfully reattached before being evaluating by B-ultrasound and fundus photography after surgery. Visual acuity was enhanced in two patients who were macularly affected. One patient had temporary diplopia and eye movement limitation after surgery. No other complications were recorded. Conclusion: This pilot study determined that foldable capsular vitreous body scleral buckling can be efficacious and safe for simple RRD. The results indicate that this surgery may be a novel alternative to the current extraocular procedures for simple RRD. Abstract : As a modification to scleral buckling surgery, we evaluated the efficacy and primary safety of treating rhegmatogenous retinal detachment by using foldable capsular vitreous body scleral buckling in five patients. The observation time after the operation was at least 12 weeks.